Soft Tissue Augmentation by Electrospun Membranes embedded With Nano-Hydroxyapatite: Histologic and Volumetric Analyses - Yu Zhu; Zuohui Xiao; Yingxin Gu; Qiang Zhi; Zhuoli Huang; Yijie Zhang; Chunan Zhang; Shichong Qiao (International Dental Journal)
Purpose: The aim of this study was to assess the histologic and volumetric alteration in gingival tissues following grafting with electrospinning collagen membranes blended with nanophased hydroxyapatite (nHA) on the buccal side of canine teeth. Methods: Four adult beagle dogs underwent hemisecting of the mandibular premolars, followed by the extraction of the mesial roots. Soft tissue augmentations were randomly conducted with collagen membranes composed of poly (L-Lactic-co-caprolactone) and porcine fibrinogen (PLCL/F-Fg), PLCL/F-Fg membranes blended with nHA (PLCL/F-Fg/nHA), or a sham-operated control. The animals were sacrificed at 12 weeks post-surgery and received volumetric analyses. Histological examinations at the meantime were carried out at five different depths below the crest (0, 1.5, 2.5, 3.5 and 5.5 mm). Results: Histological examinations showed a statistically significant increase in buccal gingival thickness between PLCL/F-Fg/20%nHA and PLCL/F-Fg (3.82 ± 1.56mm vs 1.78 ± 0.20mm (at 3.5 mm); 4.23 ± 0.63mm vs 1.80 ± 0.58mm (at 5.5 mm)) as well as between PLCL/F-Fg/20%nHA and PLCL/F-Fg/10%nHA (4.23 ± 0.63mm vs 1.97 ± 0.73mm (at 5.5 mm)). Volumetric analyses showed a statistically significant decrease in volume reduction between PLCL/F-Fg/20%nHA and PLCL/F-Fg (4.46 ± 2.75mm3 vs 10.27 ± 4.77mm3) as well as between PLCL/F-Fg/20%nHA and PLCL/F-Fg/10%nHA (4.46 ± 2.75mm3 vs 10.57 ± 2.88mm3). Conclusion: PLCL/F-Fg/20%nHA membranes demonstrated effectiveness in the gingival thickness augmentation on the buccal side of canine teeth at 12 weeks postsurgery. The electrospinning collagen membranes blended with nHA rendered an alternative treatment for soft tissue volume augmentations at the pontic site.